Uncertainty estimation while proceeding multi-parameter eddy current testing - Gorkunov, Borys; Lvov, Sergii; Borysenko, Yevhen (Харківський національний університет Повітряних Сил ім. Івана Кожедуба, 2018)
The article deals with the problem of non-destructive testing of metal products and shows the advantage of the multiparameter eddy current method, which allows, to determine the conductivity and magnetic permeability of test-ed object in addition to defects detection. The design and operation description of an eddy-current transducer using spatially periodic decomposition of the electromagnetic field is presented. A mathematical apparatus that allows the inverse task solation, namely to determine the parameters of the object being tested is described. A graph-analytical method for estimating the standard uncertainty of determining the parameters of a controlled object is presented, and its use is justified.

Стаття присвячена проблемі неруйнівного контролю металевих виробів та показує перевагу багатопараметрового вихрострумового методу, який дозволяє визначити провідність та магнітну проникність випробуваного об'єкта на додаток до виявлення дефектів. Наведено опис конструкції та способу підключення вихрострумового перетворювача із використанням просторово-періодичного розкладання електромагнітного поля. Описаний математичний апарат, який дозволяє вирішувати зворотну задачу, а саме визначити параметри випробуваного об'єкта. Наведено та обгрунтовано доцільність використання графічно-аналітичного методу оцінки стандартної невизначеності параметрів контрольованого об'єкта.
Оцінка невизначеності при багатопараметровому вихрострумовому контролі
Keywords: spatially-periodic decomposition; electro-magnetic field; non-destructive testing; eddy current transducer; object under test; неруйнівний контроль; просторово-періодична структура; електромагнітне поле